Gallery 4: The Zodiac Series - Ojeda, Almerindo E. (2014)
In 1585, one of the members of the Sadeler family of printers and engravers published a set of twelve engravings by Adriaen Collaert after designs by Hans Bol. These engravings were introduced by a title page which described them as "gospel emblems of the twelve celestial signs, set according to the months of the year." The title page went on to explain that "Christ gave man the celestial bodies so that he could discern through them the evolution of time begun in God (acc. to Gen. I), revoke idolatry, and arrive, through these creations, at the worship of a single Creator, setting his sights on the mystical kingdom of the heavens." The twelve emblemata engraved by Collaert were painted by Diego Quispe Tito in Cuzco in 1681 (Mesa and Gisbert 1982, I, 157). Unfortunately, the current whereabouts of three of these paintings—Taurus, Gemini, Virgo—are unknown. The engraved sources of the missing paintings are shown below in the hopes that they might lead us to their painted descendants. The paintings authored by Quispe Tito constitute the only known example of an American series of colonial paintings that is based on the signs of the Zodiac. Probably this was due to the association of the Zodiac to pagan cults that the Catholic Church was seeking to extirpate in the Americas (Mesa and Gisbert 1982, I, 157). Indeed, in his Tesoros verdaderos de las Indias (1682), the religious chronicler Juan Meléndez warned us that en Indias […] suele suceder que se vuelve a los ídolos, y a sus ritos y ceremonias antiguas […] y asi se tiene mandado, que no sólo en las iglesias, sino en ninguna parte, ni pública ni secreta de los pueblos de los Indios, se pinte el sol, la luna, ni las estrellas por quitarles la ocasión de volver (como está dicho) a sus antiguos delirios y disparates (Tord 1989, 181f). We have collected in this gallery the correspondences between the series by Collaert and the group of paintings by Diego Quispe Tito. To visit this gallery, follow the navigation panel below throughout this website. Click on the down-arrows to move through the gallery; to retrace your steps, click on the up-arrows.